The Aspects of Online Clothing Store Photo Product which Affect Consumer Decision Making - Jasson Harsojo; Elisha Lazaria; Ajaxta Chesio; Takhta Incra (Universitas Prasetiya Mulya, 2022)
Online shopping in this era is something that is already common in society, especially with the rapid growth of technology. Especially in Indonesia, the majority of the population already has access to the internet. This trend has become much more common since the rise of e-commerce in Indonesia such as Tokopedia, Shopee, and Bukalapak. Since there’s no physical appearance of the product, customers will rely on the photo of the product. Aesthetics of the photo presumably will affect the customer's intention to buy the product. This journal will cover the factors from the product's photo that will affect the consumers intention to buy the product. The product that will be covered in this journal is clothes. The methodology used for this research will be based on quantitative and qualitative research. The quantitative research was done by 9 interviewee and the qualitative research was done by 52 respondents. All of the research participants were from Indonesia. There are several hypotheses made, such as the physical appearance of the model, the lighting of the photo, editing of the photo, and also the quality of the photo will affect consumer decision making. There are several findings from this research. Better photo lighting, mix-match of the product, and detail of the product will definitely affect consumer decision making. While there’s interesting finding which is foreign model, in this case non asian models will decrease the intention to buy the product, as the customer prefers to see the model with the same physical posture so the customer is able to visualize how the clothes fit in their body. Editing is also necessary as long as it’s not affecting the clothes’ color.